GRAMMATICAL ERRORS FOUND IN DESCRIPTIVE TEXT WRITTEN BY THE STUDENTS OF X MIPA 2 AT SMA N 1 CEPIRING IN ACADEMIC YEAR 2021/2022 - Nita Agustina; Wiyaka Wiyaka; Siti Musarokah (Wawasan Pendidikan, 2023)
This final project studied the grammatical errors made by the students of 10th MIPA 2 SMA N 1 Cepiring. The objectives of the study were (1) To describe 4 types of grammatical errors in writing descriptive text made by the students of X MIPA 2 SMA N 1 Cepiring based on Dulay, Burt, and Krashen (1982) theory, (2) To find out what grammatical errors are dominantly made by the students, (3) To describe how teachers minimize the students’ grammatical errors. The design of the research was descriptive qualitative research. The subject of the research were 10th MIPA 2 SMA N 1 Cepiring. The instrument of the study were test and interview. To identify the data of errors, the writer used the theory of Dulay, Burt, and Krashen (1982), for the interview the writer used Miles and Huberman (1994) theory which consists of 3 steps: Data Reduction, Data Display, and Conclusion Drawing. The result of this research showed that: (1) the number of each errors are: errors of omission found 8 errors with 20,5% grammatical errors percentage, errors of addition found 9 errors with 23,1% grammatical errors percentage, errors of misformation found 15 errors with 38,5% grammatical errors percentage, and the last one errors of misordering found 7 errors with 17,9% grammatical errors percentage; (2) the dominant types of errors was the errors of misformation with 38,5% percentage; (3) The results of the interviews show that to minimize students' errors is by giving more practice in making sentences which focus on grammar or tense and emphasizing to the students that is normal for having some mistakes so that the students become confident of their works.